Reviews, Challenges, and Insights on Computational Methods for Network Reconfigurations in Smart Electricity Distribution Networks - El-Fergany, Attia A. (Archives of computational methods in engineering, 2024)
Power losses and voltage profiles in electricity distribution networks are a problem, particularly in developing nations. Many techniques have reportedly been used in the previous ten years to address this issue. Among other solutions, network reconfigurations (NRs) are regarded as one of the most practical. It is important to conduct a periodic update survey on this subject because the electricity radial distribution networks (RDNs) are continually evolving. Therefore, a thorough evaluation of the various techniques to address the issues with NRs along distribution networks is provided in this manuscript. There is discussion of several mathematical, traditional, heuristic-based, and machine-learning strategies. It is important to understand how the radiality is achieved as well as methods for resolving distribution load flow, particularly with greater R/X ratios. The most typical test cases used in the literature are listed. In order to enrich this review and make it useful to others, more than 200 articles (the majority of which were published in the last five years) are referenced inside the body of this text. The final conclusions and related future insights are presented. At last, this work is an invaluable resource for anyone involved in this field of study because it offers a comprehensive literary framework that can serve as the foundation for any future research on NRs and its prospective difficulties. Therefore, academics can use this framework to enhance previous formulations and approaches as well as suggest more effective models.